Análise da toxicidade de uma Fluoropirimidina em Protocolo Quimioterápico - Machado, Catrine de Souza (2019)
Introduction: Colorectal cancer (CRC) is the third most common cause of cancer in the world. In its treatment, are used chemotherapeutic agents whose toxicities influence the quality of life of these patients. Objective: Evaluate the most frequent toxicities based on the effects of 5-fluorouracil in patients with colorectal neoplasm submitted to 5-fluorouracil chemotherapy in combination with folinic acid, oxaliplatin (FOLFOX) and irinotecan (FOLFIRI). Methods: A cross-sectional study conducted in a Brazilian public institution in patients with previous diagnosis of colorectal cancer who received cycles of infusional chemotherapy for 48 hours every two weeks for a total of 12 cycles or 24 weeks of treatment. The studied variables were obtained by reviewing medical records, through a survey in the medical and statistical archive service (SAME). Results: Age ranged from 35 to 84 years old, with a mean of 60,75 years, being 56.25% of the female gender and 43.75% of the male. The most commonly observed toxicities were nausea, stomach pain and muscle weakness. No patient was in stages 0 and I, 25% (n = 4) in II, 31.25% (n = 5) in III and 43.75% (n = 7) in IV. Conclusion: It is noted that fluorpyrimidines continue to be the mainstay in the treatment of cancer. Thus, in this perspective the identification of the enzymatic activity of Dihydropyrimidine Dehydrogenase (DPD) is strongly related to the pharmacology of 5-FU, therefore, the determination of this enzyme before the beginning of therapy has been shown to be fundamental to identify patients at high risk of disease severe and life-threatening toxicity.